2005
DOI: 10.1016/j.jbusres.2004.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The RELQUAL scale: a measure of relationship quality in export market ventures

Abstract: In this article, the authors develop a new measurement scale (the RELQUAL scale) to assess the degree of relationship quality between the exporting firm and the importer. Relationship quality is presented as a high-order concept. Findings reveal that a better quality of the relationship results in a greater (1) amount of information sharing, (2) communication quality, (3) long-term orientation, as well as (4) satisfaction with the relationship. The four multi-item scales show strong evidence of reliability as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
190
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(205 citation statements)
references
References 62 publications
5
190
0
5
Order By: Relevance
“…Although relationship-specific assets imply expenditure for the exporting firm, the findings suggest that these are investments that tie the exchange partners together and enhance relationship quality (Lages, Lages, & Lages, 2005). Industrial exporting firms, therefore, should demonstrate their transaction-specific assets in an attempt to facilitate constructive conflict and broaden the relationship's time horizon.…”
Section: Discussionmentioning
confidence: 98%
“…Although relationship-specific assets imply expenditure for the exporting firm, the findings suggest that these are investments that tie the exchange partners together and enhance relationship quality (Lages, Lages, & Lages, 2005). Industrial exporting firms, therefore, should demonstrate their transaction-specific assets in an attempt to facilitate constructive conflict and broaden the relationship's time horizon.…”
Section: Discussionmentioning
confidence: 98%
“…Based on popular literature and mainstream research of marketing and business, Roberts et al (2003) advocated an attributional definition, and propose that conceptual meanings of constructs are anchored by the properties and/or attributes they possess. Consequently it is widely believed that RQ is attributed as a high order construct made of several distinct though related dimensions or attributes, which can deliver an evaluation tool for working relationship status (Ashnai et al, 2009;Bahar et al, 2009;Jelodar et al, 2015b;Lages et al, 2005). Attributes such as ethical behaviour, satisfaction, commitment, opportunism, and trust have been considered as RQ attributes or dimensions (Roberts et al, 2003).…”
Section: Relationship Quality: Definition and Theorymentioning
confidence: 99%
“…Sanchez-Franco et al [22] investigated relationship quality between customers and service providers and found that it positively influenced loyalty towards the service provider. Lages et al [16] developed a scale (RELQUAL) to measure relationship quality in the export market. Similarly, Rauyruen and Miller [21] studied relationship quality in the B2B context and found that it positively influenced business customer loyalty.…”
Section: Conceptual Backgroundmentioning
confidence: 99%